2023
DOI: 10.1039/d3nr01863f
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the optical stability of CsPbBr3 with different dimensions (0D, 1D, 2D, 3D) under thermal environments

Abstract: The thermal stability of phosphor materials had long been a bottleneck in their commercialization. Nowadays, cesium lead halide perovskite CsPbBr3 was considered as a potential replacement for the next generation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Especially, thermally induced permanent traps lead to slight crystal structure distortions, and thus trigger the irreversible fluorescence quenching. 34 Besides, the PL emission peak exhibits a slight blue shift during heating and is restored to the initial position during subsequent cooling down. This blue shift of PL emission peak is attributed to a stabilization of out-of-phase band-edge states as the lattice expands.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Especially, thermally induced permanent traps lead to slight crystal structure distortions, and thus trigger the irreversible fluorescence quenching. 34 Besides, the PL emission peak exhibits a slight blue shift during heating and is restored to the initial position during subsequent cooling down. This blue shift of PL emission peak is attributed to a stabilization of out-of-phase band-edge states as the lattice expands.…”
Section: Resultsmentioning
confidence: 96%
“…The difference between the final PL intensity and the initial one is defined as irreversible fluorescence quenching, which is related to the traps produced by thermal activation. Especially, thermally induced permanent traps lead to slight crystal structure distortions, and thus trigger the irreversible fluorescence quenching . Besides, the PL emission peak exhibits a slight blue shift during heating and is restored to the initial position during subsequent cooling down.…”
Section: Resultsmentioning
confidence: 99%
“…5c). 40 Subsequently, the time-resolved PL spectra of pure Cs 2 AgIn 0.98 Bi 0.02 Cl 6 NCs showed that the lifetime was shorter than that of Cs 2 AgIn 0.98 Bi 0.02 Cl 6 @KIT-6 NCs (Fig. 5d), which suggested that their non-radiative recombination ratio was higher (Table S4, ESI†).…”
Section: Resultsmentioning
confidence: 98%
“…23 However, the deposition of single-layer graphene over a large device area is challenging, 24−27 and the curing temperature (130 °C) of graphene can cause degradation of CsPbBr 3 NCs. 16,28 An ideal approach to prevent anion exchange should have the following qualities: (i) prevention of anion migration for a longer duration, (ii) efficient charge transport, (iii) chemically stable, and (iv) an optically transparent layer. Present methods of preventing anion migration in LHPs lack several of these qualities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Instead of a solution-based technique, Hautzinger et al developed a single-layer graphene (SLG) ion-blocking layer on top of the CsPbBr 3 NC film, which showed negligible anion diffusion for more than a month with minor broadening and shifts in PL peaks while allowing charge transfer . However, the deposition of single-layer graphene over a large device area is challenging, and the curing temperature (130 °C) of graphene can cause degradation of CsPbBr 3 NCs. , …”
Section: Introductionmentioning
confidence: 99%